PENGARUH MOTIVASI INTRINSIK TERHADAP KEPUASAN KERJA DAN KINERJA KARYAWAN PADA PT BUSSAN AUTO FINANCE - Widyaputra, Ketut Andika; Dewi, A.A Sagung Kartika (E-Jurnal Manajemen; Vol 7 No 1 (2018)DO - 10.24843/EJMUNUD.2018.v7.i01.p04, 2018)
Performance is the result of work produced both in terms of quality and quantity of work and can be accounted for in accordance with its role within the organization or company, and accompanied by the ability, skill, and skill in completing the work within a certain period of time. This research was conducted at PT Bussan Auto Finance Branch of Denpasar by using 73 employees as research respondents. Sample determination technique used in this research is saturated sample technique. Data collection was done through interviews and questionnaires. Data analysis technique used in this research is path analysis processed using SPSS software. Based on the results of the analysis, this study shows that intrinsic motivation has a significant positive effect on job satisfaction. This shows that giving good intrinsic motivation to employees can increase employee work satisfaction to the company. Job satisfaction has a significant negative effect on employee performance. The higher the job satisfaction is perceived, the higher the employee's performance against his company. Intrinsic motivation has a significant positive effect on employee performance. Giving good intrinsic motivation to employees can improve employee performance against the company.   Keywords: intrinsic motivation, job satisfaction, employee performance